Policy and planning for large infrastructure projects : problems, causes, cures - Flyvbjerg, Bent, 1952- 1952- (Policy research working paper, 2005)
"This paper focuses on problems and their causes and cures in policy and planning for large infrastructure projects. First, it identifies as the main problem in major infrastructure development pervasive misinformation about the costs, benefits, and risks involved. A consequence of misinformation is massive cost overruns, benefit shortfalls, and waste. Second, the paper explores the causes of misinformation and finds that political-economic explanations best account for the available evidence: planners and promoters deliberately misrepresent costs, benefits, and risks in order to increase the likelihood that it is their projects, and not the competition's, that gain approval and funding. This results in the "survival of the unfittest," where often it is not the best projects that are built, but the most misrepresented ones. Finally, the paper presents measures for reforming policy and planning for large infrastructure projects, with a focus on better planning methods and changed governance structures, the latter being more important. "--World Bank web site